Clustering Regency and City in East Java Based on Population Density and Cumulative Confirmed COVID-19 Cases - Khusnia Nurul Khikmah; A'yunin Sofro (ComTech: Computer, Mathematics and Engineering Applications, 2021)
Coronavirus is a big family of viruses that causes acute respiratory syndrome and mediates human-to-human by the environment. A factor that affects the spread of infectious diseases is population density. Therefore, it is necessary to study the effect of population density on infectious diseases like COVID-19. The research analyzed the effect of the population density of each regency in East Java on cumulative confirmed COVID-19 cases until December 9, 2020. The research applied quantitative method using the agglomerative hierarchical clustering method. The clustering method included single, average, and complete linkages. The results of clustering using single linkage and average linkages have the same results for the population density of Jember Regency. This regency has the lowest effect for the cumulative confirmed COVID-19 cases. Then, complete linkage obtains that Banyuwangi Regency and Gresik Regency has the population density with the lowest effect for the cumulative number of confirmed COVID-19 cases. The results of clustering with single, average, and complete linkages have the same results for population density with a big effect on the cumulative number of confirmed COVID-19 cases in Surabaya City. The results of best clustering regencies or cities that population density affects the number of